REKONSTRUKSI SISTEM PERADILAN PIDANA INDONESIA DALAM PERSPEKTIF KEMANDIRIAN KEKUASAAN KEHAKIMAN - Pujiyono Pujiyono (Faculty of Law, Universitas Diponegoro, 2012)
Criminal justice system as a tool of law enforcement, didn't work optimally in Indonesia. It often being used by executive power because its position and function didn't independent and subordinated by executive power. Judicial power is an independent power, but other subsistem in CJS such as investigative power, prosecution power, and Executors power structurally and functionally are under executive power, and as result that their roles as a power instrument to service power's interest. This research purpose to set ideal format in integrated CJS working , to manifest judicial power in the independency and integrated criminal law enforcement through reconstruction and reorientation of criminal justice system construction, substantial and cultural. Main object in this research is criminal law enforcement policy, juridical normative and sociological approach, primary and secondary data as a main data to qualitative analyzing. The result of this research show that function of subsystem in criminal justice system (such as investigation, prosecution, and execution power ) have not show independent yet, cause of under the executive power. Anyway judicial power is set as independent power out of executive power, in organizationing, budgeting, staffing, and carrier system under one roof system that subordinated by Supreme Court . Here CJS is unsystemic but partially and fragmentair. This situation result subsytem rivality and in the end can be barrier in CJS performances. There is policy measures to implement integrally of independency criminal justice system by systemic approach to reset related policy in the law substance, the law structure and the law culture. Keywords : reconstruction, criminal justice system, independency and judicial power.